Cellular and Molecular Responses of Cultured Neurons to Stressful Stimuli. Issue 3 (1st July 2011) - Chen, Jun; Pan, Hongna; Lipsky, Robert H.; Pérez-Gómez, Anabel; Cabrera-Garcia, David; Fernández-Sánchez, Maria Teresa; Novelli, Antonello; Marini, Ann M.
Synaptic function is critical for the brain to process experiences dictated by the environment requiring change over the lifetime of the organism. Experience-driven adaptation requires that receptors, signal transduction pathways, transcription and translational mechanisms within neurons respond rapidly over its lifetime. Adaptive responses communicated through the rapid firing of neurons are dependent upon the integrity and function of synapses. These rapid responses via adaptation underlie the organism's ability to perceive, learn, remember, calculate and plan. Glutamate, the endogenous neurotransmitter required for physiological excitation in the brain, is critically involved in neuronal adaptive responses and in the pathophysiology of neurodegenerative disorders. Using neuronal experimental systems, we will discuss how compounds with low dose effects mediated via glutamate receptors can result either in a neuroprotective or neurotoxic response. Because the brain has evolved to respond rapidly to environmental cues, exposure of neurons to stressful stimuli can result in a pivotal response toward either synaptic adaptation or dysfunction and neuronal cell death. Understanding how neurons adapt to stressful stimuli will provide important clues toward the development of strategies to protect the brain against neurodegeneration.